The Effect of Career Planning and Employee Loyalty on Increasing Work Achievement - Widarko, Agus (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This research was conducted at Madrasah XYZ, with quantitative research. The number of respondents in this study was 46 people, which is the entire population of this study, namely teachers and staff at XYZ Madrasah. The data collection technique used a questionnaire that was distributed directly to the respondents, who then processed the data or answers of the respondents using statistics. The steps are to test the validity, reliability test, and classic assumption test which consists of the normality test, linearity test, heteroscedasticity test, and multicollinearity test. The next step is to test the data analysis using multiple linear regression and the last test is to test the research hypothesis. Partially, career planning has a positive effect on work performance, but the effect is greater on employee loyalty on work performance. Simultaneously or together career plans and employee loyalty have a significant and positive effect on work performance.